Pengembangan Kewirausahaan Santri Pada Balai Latihan Kerja Komunitas Pesantren Al-Istianah Pati Jawa Tengah - Sukandar (EL- Hayah, 2023)
This study aims to determine (1) The process of program implementation at the Balai Latihan Kerja Komunitas Pesantren Al-Istianah Pati Central Java (2) Factors that influence the development of sustainable entrepreneurship of students after the implementation of the Balai Latihan Kerja Komunitas Pesantren Al-Istianah Pati Central Java program. Researchers used descriptive-qualitative methods with data collection techniques through interviews, observation and documentation. Data validity checks using data triangulation techniques and data analysis using data reduction, data display, and conclution drawing/verification techniques. The results showed: (1) the implementation of the Junior graphic design training program at BLK Komunitas Pesantren Al-Istianah Pati has been running effectively in accordance with the technical instructions from the Indonesian Ministry of Manpower in developing the knowledge and skills of trainee santri in the field of graphic design competence (2). The sustainable development of santri entrepreneurship after the implementation of the training program at BLKK Al-Istianah is influenced by several factors, namely: factors of vision, mission and organizational goals, training curriculum, training instructors and graduate participants. Based on these findings, this study recommends the need for collaborative and synergic steps from various parties in the form of further programs at BLKK Al-Istianah related to improving business skills, strengthening business infrastructure, capital support, mentoring and mentoring as well as building networks and business partnerships so that later santri graduates can truly be motivated and entrepreneurial in developing independent and sustainable businesses.